The role and correlation of IL-35 and type II intrinsic lymphocytes in children with allergic rhinitis - Huang, Ligao; Zhao, Min; Luo, Qian; Liang, Kuai; iu, Cui L (Cellular and Molecular Biology, 2021)
To investigate the role and correlation of IL-35 and ILC2 in children with allergic rhinitis. 50 cases of children with allergic rhinitis admitted to our hospital from February 2018 to March 2020 were selected as the research subjects and set as the study group. During the same period, 50 cases of normal children admitted to our hospital for physical examination were selected as the control group. The differences in the expression of IL-35 and ILC2 between the two groups and the correlation with the severity of allergic rhinitis were compared. In BMI, the study group was significantly lower than the control group, and the difference was statistically significant (P<0.05). IL-35 in the study group was significantly lower than that in the control group, while ILC2, IL4+ILC2, IL-5+ILC2, IL-13+ILC2, IgE and ECP in the study group were significantly higher than those in the control group, the difference was statistically significant (P<0.05). Pearson correlation analysis showed a moderate negative correlation between TNSS score and IL-35 (r =-0.642, P<0.05), was positively correlated with ILC2, IL4+ILC2, IL-5+ILC2, IL-13+ILC2, ECP (r =0.745, 0.713, 0.725, 0.769, 0.746, P<0.05), and was strongly correlated with IgE (r =0.952, P<0.05). Also, It was positively correlated with TGF-?1 (r =0.513, P<0.05). IL-35 was strongly negatively correlated with ILC2, IL4+ILC2, IL-5+ILC2, IL-13+ILC2 (r =-0.845, -0.812, -0.805, 0.823, -0.854, P<0.05). Was negatively correlated with ECP and TGF-?1 (r =-0.795, -0.543, P<0.05). ILC2 was strongly correlated with IgE (r =0.812, P<0.05), and moderately positively correlated with ECP and TGF-?1 (r =0.642, 0.541, P<0.05). ROC curve was used to evaluate the diagnostic value. The results showed that among the five indicators, IgE had the highest sensitivity of 92.23%, while IL-35 had the highest specificity of 92.56%. However, the combined area, sensitivity and specificity of the five indicators were the highest, 0.962, 95.18% and 94.25%, respectively (P<0.05). Both IL-35 and type II intrinsic lymphocytes are highly correlated with the severity of allergic rhinitis in children, the former is negatively correlated with the latter is positively correlated. The detection of these indexes in clinical practice can be helpful for clinical diagnosis.